ANALISIS FRAMING MODEL PAN DAN KOSICKI DALAM BERITA PELECEHAN SEKSUAL ANAK PANTI ASUHAN PADA MEDIA ONLINE CNN INDONESIA DAN KUMPARAN.COM - Hikmatunisa, Azizah; Setiawan, Hendra (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This study aims to determine how the media frames the news it writes. The method used in this study is a qualitative descriptive method. The subjects in this study were two online news media, namely CNN Indonesia and Kumparan.com, with the object of research in the form of one news text from each media; "Social Minister Risma Complains Harassment of Children at an Orphanage in Malang to the Criminal Investigation Unit," and "Police Detain 10 Perpetrators of Obscenity and Mistreatment of Orphans in Malang". The results of the framing analysis of the two media found some differences, especially in the syntactic elements used. Online news media CNN Indonesia and Kumparan.com have differences and similarities, especially in the news titles presented. CNN Indonesia media uses a choice of words that do not offend the victim, while the Kumparan.com media uses a selection of pretty offensive dishes to the victim's feelings. The 5W + 1H elements in both media are complete and can explain the overall content of the news. Both of these media also have a coherent thematic structure between paragraphs, but both of them still use pronouns in mentioning their sources. The images used in the rhetorical construction of the two media have their respective meanings.